PENGARUH FAKTOR INSTRINSIK, PERAN INDIVIDU, PENGEMBANGAN KARIR, HUBUNGAN PEKERJAAN TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS KETAHANAN PANGAN KABUPATEN BOJONEGORO - jurnalmap map; Revi Puspitasari; Mei Indrawati; Hidayat ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT The purpose of this study was to analyze the influence of existing factors, the role of individuals, career development and job relations partially and simultaneously to job satisfaction in the Food Security Department of Bojonegoro Regency. This research method is a quantitative approach. The population in this study was in the Food Security Department of Bojonegoro Regency, which lived 31 people. The sampling technique uses a sampling census, that is, all members of the population are used as sample research, namely 30 independent researchers. The results showed partially the variables that significantly influence job satisfaction are individual individuals, career development, and relationships, while the intrinsic factor variable is not significant to job satisfaction at the Bojonegoro Regency Food Security Department. Keywords: intrinsic, individual role, career development, and significant relationship to the performance of employees of the Bojonegoro Food Security Department. Among intrinsic factors, individual roles, career development, and job relations that are oriented towards career development. Keywords: intrinsic factors, individual roles, career development, job relations, job satisfaction